2015
DOI: 10.1016/j.neuron.2014.12.048
|View full text |Cite
|
Sign up to set email alerts
|

High Salt Intake Increases Blood Pressure via BDNF-Mediated Downregulation of KCC2 and Impaired Baroreflex Inhibition of Vasopressin Neurons

Abstract: Summary The mechanisms by which dietary salt promotes hypertension are unknown. Previous work established that plasma [Na+] and osmolality rise in proportion with salt intake and thus promote release of vasopressin (VP) from the neurohypophysis. Although high levels of circulating VP can increase blood pressure, this effect is normally prevented by a potent GABAergic inhibition of VP neurons by aortic baroreceptors. Here we show that chronic high salt intake impairs baroreceptor inhibition of rat VP neurons th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
170
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(184 citation statements)
references
References 54 publications
14
170
0
Order By: Relevance
“…Based on our data described above, we then evaluated whether activated microglia contribute to ANG II-evoked ROS production in the PVN. To this end, we performed similar DHE experiments in slices incubated in either 1) regular aCSF, 2) aCSF ϩ ANG II (1 M), or 3) aCSF ϩ ANG II ϩ the microglial inhibitor minocycline (100 M) (15,86). As previously observed, ANG II significantly increased DHE staining compared with control aCSF (n ϭ 4/group, Fig.…”
Section: Ang Ii-mediated Ros Within the Pvn Involves Activated Microgliasupporting
confidence: 62%
See 1 more Smart Citation
“…Based on our data described above, we then evaluated whether activated microglia contribute to ANG II-evoked ROS production in the PVN. To this end, we performed similar DHE experiments in slices incubated in either 1) regular aCSF, 2) aCSF ϩ ANG II (1 M), or 3) aCSF ϩ ANG II ϩ the microglial inhibitor minocycline (100 M) (15,86). As previously observed, ANG II significantly increased DHE staining compared with control aCSF (n ϭ 4/group, Fig.…”
Section: Ang Ii-mediated Ros Within the Pvn Involves Activated Microgliasupporting
confidence: 62%
“…To this end, we performed ex vivo assays using acute hypothalamic slices containing the PVN, which were obtained from control rats as well as from TLR4-sufficient C3H/OuJ (TLR4-sufficient) and TLR4-deficient C3H/HeJ (TLR4-deficient) mice (56). We found that ANG II (1 M) significantly increased the degree of activated microglia (shown as significantly enhanced staining density for IBA1 within the PVN) (15,71) in rat slices compared with control aCSF (ϳ65% increase from 9.8 Ϯ 1.1% to 16.2 Ϯ 1.4%, n ϭ 10, P Ͻ 0.001; Fig. 1, A-E).…”
Section: Ang Ii-mediated Pvn Microglial Activation Requires Functionamentioning
confidence: 99%
“…On the other hand, it is conceivable that MRS5698 may impact BDNF/TrkB/KCC2 signaling by inhibiting the release of BDNF from glial cells as a parallel mechanism to the phosphorylation events we observe in A 3 AR-mediated restoration of GABAergic function. We have previously demonstrated the capacity of A 3 AR activation to attenuate astrocyte reactivity and neuroinflammatory response in chemotherapy-induced peripheral neuropathy and additionally, A 3 AR activation may provide neuroprotection by inhibiting the reactive chemotaxis of microglia (Choi et al, 2011). As such, it is possible that an A 3 AR-mediated reduction in glial activation could preclude glial BDNF release and relieve TrkB-mediated alterations in GABA signaling in contribution to the restoration of GABA signaling that we have observed.…”
Section: Discussionmentioning
confidence: 63%
“…It is unlikely that MRS5698 acts directly on TrkB as an off-target because the observations in our manuscript are not consistent with the effects of a TrkB antagonist: in our studies, we have identified Ser940 on KCC2 (Lee et al, 2007) as a critical site of A 3 AR-mediated regulation. In contrast, TrkB has only been documented to modify Tyr515 on KCC2 in the CNS (Rivera et al, 2004;Choe et al, 2015), and this phosphorylation event produces transporter internalization rather than an increase in transporter activity. Additionally, TrkB activity is not known to regulate the phosphorylation of GAD65 or GAT-1; it has been suggested that TrkB influences these enzymes through a CREB-dependent mechanism of transcriptional regulation (Sanchez-Huertas and Rico, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, it has been recently demonstrated that long-term elevation of BDNF in the paraventricular nucleus of the hypothalamus has a major impact on central regulation of sympathetic activity, blood pressure and heart rate which is mediated by ANG II/angiotensin type 1 receptor and angiotensin/Mas [35]. Dietary high salt intake promotes vasopressin release which contributes to the elevation of arterial pressure through BDNF-TrkB-GABAergic signaling system [3537].…”
Section: Discussionmentioning
confidence: 99%